Antagonizing αvβ3 Integrin Improves Ischemia-Mediated Vascular Normalization and Blood Perfusion by Altering Macrophages - Li, Yongjie; Gao, Qian; Shu, Xin; Xiao, Lamei; Yang, Yan; Pang, Ningbo; Luo, Yulin; He, Jing; Zhang, Liping; Wu, Jianbo (Frontiers in Pharmacology, 2021)
Background: αVβ3 integrin has been implicated in the physiological processes and pathophysiology of important angiogenesis-related disorders; however, the preclinical and clinical data on integrin αVβ3 antagonists have not demonstrated improved outcomes. Thus, a significant opportunity exists to take advantage of the useful properties of these drugs. Our goal was to test the hypothesis that inhibition of αVβ3 integrin improves blood flow in a mouse hindlimb ischemia model. Methods: In this study, we examined the effect of cilengitide, an αVβ3/αVβ5 integrin-specific RGD-mimetic cyclic peptide, on blood perfusion and angiogenesis after hindlimb ischemia. Blood flow was measured using Laser Doppler Scanner. Vascular density, and macrophages infiltration were examined by immunofluorescence. Macrophage polarization was measured by quantitative real time PCR. Results: We found that low-dose, not high-dose, cilengitide increased blood flow perfusion, capillary formation, and pericyte coverage, accompanied by an accumulation of macrophages and increased expression of the chemokine (C-C motif) ligand 2 (CCL2) chemokine monocyte chemoattractant protein 1 (MCP-1) in ischemic muscles. Macrophage depletion using clodronate liposomes resulted in a reduction in low-dose cilengitide-induced blood flow perfusion, macrophage accumulation, pericyte coverage, and MCP-1CCL2 expression. Finally, in vitro assays showed that low-dose, not high-dose, cilengitide increased macrophage migration. Conclusion: These studies identified a novel role of the inhibition of αVβ3 integrin in modulating ischemia-induced angiogenesis, possibly through effects on macrophage infiltration and polarization, and revealed αVβ3 integrin inhibition to be a promising therapeutic strategy for peripheral artery disease.